Optimalisasi Pemasaran Digital untuk Meningkatkan Daya Saing P4S Tani Makmur Jaya Blitar - Fatmawati, Erlin Widya; Dita Serdani, Army; Puspitorini, Palupi; Izati, Nazla Haqqul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Digital marketing needs to be implemented immediately in every business entity as a strategic approach to promote products, services, or brands to the targeted audience. The main problems faced by the partner include a lack of digital marketing skills, suboptimal use of social media, and limited integration with e-commerce platforms. P4S Tani Makmur Jaya in Blitar strives to enhance the reach and effectiveness of agricultural product marketing. This outreach activity discussed the use of various platforms such as Instagram, Facebook, and TikTok, which, although available, had not been utilized to their full potential. In addition, integration with e-commerce platforms such as Tokopedia and Shopee was also considered a way to expand market access. The training method used included direct material delivery to participants and hands-on creation of e-commerce accounts using mobile phones. As a result of this community service activity, participants successfully created several social media and e-commerce accounts such as Shopee, TikTok, Tokopedia, and Facebook. Participants, under the guidance of the facilitators, also succeeded in producing promotional videos and photos for their e-commerce accounts. Sales through the Shopee account successfully reached customers outside Blitar, particularly for organic fertilizer products. The implementation of digital marketing is expected to increase the competitiveness of the P4S Tani Makmur Jaya Group in Blitar, create new opportunities, and strengthen its position in the digital market.